Aplikasi EViews 10 student lite dengan analisis data panel pada mahasiswa Program Studi Agribisnis - Abd. Rahim; Diah Hastuti; Firmansyah Firmansyah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
EViews 10student liteprogram is used as a tool for analysis panel data of community service activities. The purpose of this activity is expected after participants follow this training is that students independently understand the processing techniques of panel data analysis with the EViews 10 program and can make decisions in analysis the results and discussion of research. The results of the identification of the problem are the Agribusiness Study Program Students of the Faculty of Agriculture, Universitas Muhammadiyah Makassar facing problems in inputting data into the research data processing program and interpreting the output of research data relating to time-series data and cross-sections as panel data that has been processed with EViews 10. From the training implementation activities found that of the 21 trainees namely Agribusiness Program students as many as 12 people were able and skilled in processing and interpreting the output data of econometric analysis with the EViews program 10. The expected output after participants took part in the training was that students independently understood the processing techniques in inputting panel econometric data analysis with the EViews 10 program.